Effects of steric hindrance and electron density of ester prodrugs on controlling the metabolic activation by human carboxylesterase. (June 2021) - Takahashi, Masato; Hirota, Ibuki; Nakano, Tomoyuki; Kotani, Tomoyuki; Takani, Daisuke; Shiratori, Kana; Choi, Yura; Haba, Masami; Hosokawa, Masakiyo
Abstract: Carboxylesterase (CES) plays an important role in the hydrolysis metabolism of ester–type drugs and prodrugs. In this study, we investigated the change in the hydrolysis rate of hCE1 by focusing on the steric hindrance of the ester structure and the electron density. For 26 kinds of synthesized indomethacin prodrugs, the hydrolytic rate was measured in the presence of human liver microsomes (HLM), human small intestine microsomes (HIM), hCE1 and hCE2. The synthesized prodrugs were classified into three types: an alkyl ester type that is specifically metabolized by hCE1, a phenyl ester type that is more easily metabolized by hCE1 than by hCE2, and a carbonate ester type that is easily metabolized by both hCE1 and hCE2. The hydrolytic rate of 1-methylpentyl (hexan–2–yl) ester was 10–times lower than that of 4–methylpentyl ester in hCE1 solution. hCE2 was susceptible to electron density of the substrate, and there was a difference in the hydrolysis rate of up to 3.5–times between p -bromophenyl ester and p -acetylphenyl ester. By changing the steric hindrance and electron density of the alkoxy group, the factors that change the hydrolysis rate by CES were elucidated.